ONLINE LEARNING MANAGEMENT AT SMA PGII 2 BANDUNG CITY - Nuroni, Enoh; Syah, Muhibbin; Erihadiana, Mohamad (Pusat Penerbitan Universitas (P2U) Unisba, 2023)
Through this research, it is possible to explore and analyze ICT managerial in SMA PGII 2 Bandung City, including policy, availability, utilization and development of ICT in the educational process. It is hoped that the excavation results and descriptions will provide benefits, both theoretically and practically. Theoretically the results of this study can become the basis for developing scientific insights related to ICT management in Islamic educational institutions; allows it to be used as one of the conceptual operationalization guidelines; theoretical study material to find patterns of sustainable ICT development. Practical Benefits, findings and studies can make a positive contribution to efforts to improve the quality of ICT management at SMA PGII 2 Bandung City which are still in need of improvement; can also be used as material for consideration in making institutional ICT development and utilization policies; It is hoped that it can also be a reference for other Islamic educational institutions that have similarities or the same Islamic vision and mission in the implementation of ICT management.